2014
DOI: 10.1186/1756-3305-7-94
|View full text |Cite
|
Sign up to set email alerts
|

TcI/TcII co-infection can enhance Trypanosoma cruzi growth in Rhodnius prolixus

Abstract: BackgroundRhodnius prolixus is an obligate haematophagous insect and one of the most important vectors of Trypanosoma cruzi, the causative agent of Chagas disease in the Americas. T. cruzi is a highly variable parasite which is not transmitted in the same efficiency by the different triatomine vectors. Because different T. cruzi genotypes are aetiopathologically divergent, further elucidation of the transmission abilities of different Chagas disease vectors is extremely important.FindingsIn the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…This parasite concentration is similar to that used in several other published studies of T. cruzi infection in triatomines, 9,44,46,50,[54][55][56][57][58][59] and blood meals taken by triatomines at this parasite concentration lead to infective doses that fall within the range of peak parasitemias observed in mice and guinea pigs experimentally infected with T. cruzi. 25,27,[60][61][62][63] Insect infection: insect preparation and feeding.…”
Section: Methodssupporting
confidence: 54%
“…This parasite concentration is similar to that used in several other published studies of T. cruzi infection in triatomines, 9,44,46,50,[54][55][56][57][58][59] and blood meals taken by triatomines at this parasite concentration lead to infective doses that fall within the range of peak parasitemias observed in mice and guinea pigs experimentally infected with T. cruzi. 25,27,[60][61][62][63] Insect infection: insect preparation and feeding.…”
Section: Methodssupporting
confidence: 54%
“…However, these interactions can be recent, as seems to occur as shown here with M. gajardoi and T. cruzi DTUs TcVI, which diverged very recently. Finally, since not all triatomine species develop different T. cruzi DTUs, this suggests that triatomines of a different genus rather than species of the same genus are differently adapted to each T. cruzi DTU (Mejía-Jaramillo et al 2009, Araújo et al 2014. The different microbiota present in triatomine guts of different genera seem to contribute to this interesting and epidemiologically relevant parasite-invertebrate interaction (Da Mota et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The term ''discrete typing unit'' (Tibayrenc 1998) was proposed to describe sets of stocks that are genetically more similar to each other than to any other stock and are identifiable by common molecular markers sometimes referred to as ''tags.'' Experimental infections have demonstrated in pioneer studies that not all T. cruzi DTUs succeed in growing and completing their development in all triatomine species (Garcia et al 1982, Azambuja et al 1989, Mello et al 1996, Urrea et al 2005, Araújo et al 2007, Mejía-Jaramillo et al 2009,Vallejo et al 2009, Araújo et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In studies with another species of the same genus, R. prolixus, the findings indicated that some T. cruzi strains did not develop within its intestinal tract to produce metacyclic trypomastigotes, but it was able to maintain parasites in its rectal lumen 39,48,49 . In many cases, under our experimental conditions, infection of the insect was only proven by PCR, demonstrating the greater capacity of detection of this technique when compared to the others.…”
Section: Dworak Es Et Al -Interaction Of T Cruzi With Triatominementioning
confidence: 94%